Backward Surface Wave Propagation and Radiation along a One-Dimensional Folded Cylindrical Helix Array - Bin Xu; Yang Li (International Journal of Antennas and Propagation)
Wave propagation along a closely spaced folded cylindrical helix (FCH) array is investigated for the purpose of designing compact array for energy transport and antenna radiation. It is found that the height of this surface wave guiding structure can be decreased from 0.24λ0 to 0.06λ0 by replacing the monopole element with the FCH. Both the propagation constant and the mode distribution of the dominant wave mechanism are extracted by ESPRIT algorithm, which indicates that a backward propagating surface wave is supported by the array structure. A compact backfire FCH antenna array is designed and measured based on the identified dominant wave mechanism.